EFFECT OF ORGANIC MANURES AND INORGANIC PHOSPHORUS FERTILIZERS ON AVAILABLE NUTRIENT STATUS OF SOIL UNDER CHICKPEA CULTIVATION - G. VENKATESWARA RAO, CH. SUJANI RAO, P. VENKATA SUBBAIAH and M. SREE REKHA (The Journal of Research ANGRAU, 2020)
The field experiment was conducted during Rabi, 2018 in randomized block design on clayey soils tostudy the effect of organic manures and inorganic phosphorus fertilizers on available nutrient status of soilunder chickpea (variety JG-11) cultivation. Application of 100% RDP through BGD + Microbial Consortiumsignificantly increased the availability of nitrogen, phosphorus content of the soil. However, there was nosignificant increase in the availability of potassium, sulphur, iron, copper and manganese. The availability ofzinc increased significantly at all the stages of the crop.